2007
DOI: 10.1093/sleep/30.2.213
|View full text |Cite
|
Sign up to set email alerts
|

Comorbidity of Chronic Insomnia With Medical Problems

Abstract: This study demonstrates significant overlap between insomnia and multiple medical problems. Some research has shown it is possible to treat insomnia that is comorbid with select psychiatric (depression) and medical (eg, pain and cancer) disorders, which in turn increases the quality of life and functioning of these patients. The efficacy of treating insomnia in many of the above comorbid disorders has not been tested, indicating a need for future treatment research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

32
423
4
28

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 743 publications
(514 citation statements)
references
References 25 publications
32
423
4
28
Order By: Relevance
“…A bidirectional link exists between insomnia and hypertension; 43% of insomnia patients have hypertension, compared to 19% among good sleepers; 44% of hypertensive patients have insomnia, compared to 19% among normotensive patients (Thase, 2005; Taylor et al, 2007; Roth, 2009; Hoevenaar‐Blom et al, 2011). Nocturnal hypertension is significantly higher in older than younger patients (63.1 vs. 41.1%).…”
Section: Melatonin In the Treatment Of Circadian Rhythm And Sleep Dismentioning
confidence: 99%
“…A bidirectional link exists between insomnia and hypertension; 43% of insomnia patients have hypertension, compared to 19% among good sleepers; 44% of hypertensive patients have insomnia, compared to 19% among normotensive patients (Thase, 2005; Taylor et al, 2007; Roth, 2009; Hoevenaar‐Blom et al, 2011). Nocturnal hypertension is significantly higher in older than younger patients (63.1 vs. 41.1%).…”
Section: Melatonin In the Treatment Of Circadian Rhythm And Sleep Dismentioning
confidence: 99%
“…The brain requires sleep in order for energy stores to be restored (Porkka-Heiskanen, Kalinchuk, Alanko, Urrila, & Stenberg, 2003) and research has shown an association between chronic poor sleep and a multitude of different health impairments, such as self-reported coronary heart disease (Schwartz, Anderson, Cole, Cornin-Huntley, Hays, & Blazer, 1999), gastrointestinal problems, high blood pressure, neurological disorders (Taylor, Mallory, Lichstein, Durrence, Riedel, & Bush, 2007), cardiovascular disease (CVD), diabetes, obesity and depression (Akerstedt, 2006). Performance is also negatively impacted by sleep loss and sleep disturbance and sleep loss can result in increased fatigue, mood changes, and impairment of the immune system (Harrison & Horne, 1999;Rogers, Szuba, Staab, Evans, & Dinges, 2001).…”
Section: Work-related Rumination and Recovery From Workmentioning
confidence: 99%
“…7,8 The common co-occurrence of insomnia with other conditions is an important consideration when examining HCU and associated costs as the rates of insomnia occurring in the context of other common medical and psychiatric conditions are much higher than that in the general population. 9,10 For example, an epidemiological study revealed that approximately 38% of individuals with a comorbid condition exhibited insomnia compared to only 8% of individuals without a comorbid condition. 9 Individuals with comorbid insomnia and major depressive disorder have demonstrated significantly greater direct health care costs (i.e., greater number of overall outpatient physician visits, depressionrelated visits, and a greater number of antidepressant prescriptions) than individuals with major depressive disorder alone.…”
Section: S C I E N T I F I C I N V E S T I G a T I O N Smentioning
confidence: 99%
“…9,10 For example, an epidemiological study revealed that approximately 38% of individuals with a comorbid condition exhibited insomnia compared to only 8% of individuals without a comorbid condition. 9 Individuals with comorbid insomnia and major depressive disorder have demonstrated significantly greater direct health care costs (i.e., greater number of overall outpatient physician visits, depressionrelated visits, and a greater number of antidepressant prescriptions) than individuals with major depressive disorder alone. 10 A recent study by Bramoweth and colleagues provides support for increased costs related to comorbid insomnia.…”
Section: S C I E N T I F I C I N V E S T I G a T I O N Smentioning
confidence: 99%